The colours of Belgium: red devils and the representation of diversity. Issue 3 (3rd July 2017) - Martiniello, Marco; Boucher, Gerard W
Abstract : This article examines the recent and huge support for the Belgian national football team, the Red Devils, during the 2014 World Cup and the 2016 football Euro tournaments. The upsurge in support for the Red Devils came as a surprise in a divided country in which national identity is very weak, and where the issue of the lack of societal integration is often discussed. The discussion shows the complexity of a super-diverse Belgian society and, relying on theories of ethnicity, identities and on approaches of everyday multiculturalism, presents several hypotheses to explain the sudden rise in support for the national football team. It also stresses the importance of market forces in developing the brand, 'Red Devils'. Altogether, the article is a plea in favour of including visual approaches in our research design to make sense of social change in super-diverse societies.